Behavioural parameters and social norm in energy use - Oh, Ching Fang (2015)
Social norm information is found to be effective in encouraging energy reduction in home residential settings. Yet, the magnitude and direction of individuals’ responses to such information provision vary according to environmental, social, time, price sensitivity and risk preferences. This study elicits these behavioural parameters from a sample of 96 undergraduates of Nanyang Technological University Hall residents through standard experimental laboratory procedures and surveys, combined with a field experiment that provides social norm treatment letters to observe the effect of heterogeneous preferences on individuals’ energy use. While not significant, we found that the average treatment effect of Social Norm is a reduction of 4.1%. Interestingly the marginal average treatment effects of Time Preference and Environmental Preference were found to be a reduction of 20.7% and 19.6% respectively. Though not significant, this was 6 times larger than the aggregate average treatment effect. This points to the importance of a follow-up study focusing on Environmental Preference and Time Preference with a greater sample size for detectable treatment effect.